The effect of stereotactic body radiotherapy (SBRT) using flattening filter‐free beams on cardiac implantable electronic devices (CIEDs) in clinical situations. Issue 6 (11th April 2020) - Aslian, Hossein; Kron, Tomas; Watts, Troy; Akalanli, Cagla; Hardcastle, Nicholas; Lonski, Peta; Montaseri, Atousa; Hay, Barry; Korte, James; Berk, Kemal; Longo, Francesco; Severgnini, Mara
Abstract: Purpose: This study focused on determining risks from stereotactic radiotherapy using flattening filter‐free (FFF) beams for patients with cardiac implantable electronic device (CIEDs). Two strategies were employed: a) a retrospective analysis of patients with CIEDs who underwent stereotactic radiosurgery (SRS)/SBRT at the Peter MacCallum Cancer Centre between 2014 and 2018 and b) an experimental study on the impact of FFF beams on CIEDs. Methods: A retrospective review was performed. Subsequently, a phantom study was performed using 30 fully functional explanted CIEDs from two different manufacturers. Irradiation was carried out in a slab phantom with 6‐MV and 10‐MV FFF beams. First, a repetition‐rate test (RRT) with a range of beam pulse frequencies was conducted. Then, multifraction SBRT (48 Gy/4 Fx) and single‐fraction SBRT (28 Gy/1 Fx) treatment plans were used for lung tumors delivered to the phantom. Results: Between 2014 and 2018, 13 cases were treated with an FFF beam (6 MV, 1400 MU/min or 10 MV, 2400 MU/min), and 15 cases were treated with a flattening filter (FF) beam (6 MV, 600 MU/min). All the devices were positioned outside the treatment field at a distance of more than 5 cm, except for one case, and no failures were reported due to SBRT/SRS. In the phantom rep‐rate tests, inappropriate sensing occurred, starting at a rep‐rate of 1200 MU/min. Cardiac implantable electronic device anomalies during and after delivering VMAT‐SBRT with a 10‐MV FFF beam were observed. Conclusions: The study showed that caution should be paid to managing CIED patients when they undergo SBRT using FFF beams, as it is recommended by AAPM TG‐203. Correspondingly, it was found that for FFF beams although there is small risk from dose‐rate effects, delivering high dose of radiation with beam energy greater than 6 MV and high‐dose rate to CIEDs positioned in close vicinity of the PTV may present issues.